Hypertonic saline and adrenaline nebulization in the treatment of bronchiolitis: a retrospective study - Shankar, Poornima; Marol, Jayalalitha S.; K., Akash B. (International Journal of Contemporary Pediatrics, 2019)
Background: Bronchiolitis is the leading cause of acute illness and hospitalization in young children. There is limited role for diagnostic laboratory or radiographic tests in typical cases of bronchiolitis. Several large recent trials have revealed lack of efficacy of either bronchodilators or corticosteroids. Novel treatment like hypertonic saline and adrenaline nebulizations need to be evaluated for their efficacy. Methods: In this retrospective case control study, we included children aged between 6 months to 2 years admitted for bronchiolitis between August 2017 till July 2018. Each of the 45 children treated with adrenaline nebulisation was assigned a child who was given hypertonic saline nebulization only matched for age and duration of symptoms. Results: 45 children given adrenaline nebulization and 45 children given only hypertonic saline nebulization were compared. Mean duration of stay for children treated with adrenaline nebulization was 5.3 days and those given hypertonic saline was 4.8 days. p value of 0.29. Conclusions: Adrenaline nebulization did not shorten hospital stay in children admitted for bronchiolitis as compared to children given hypertonic saline.